La incidencia del juego en el desarrollo psicomotríz de los niños y niñas de 4 a 5 años de los centros de educación inicial María Franco de Carrillo y Amada Agurto de Galarza del cantón Machala período lectivo 2012-2013. - Henríquez Fernández, Fanny María (2015)
This research was conducted in early education centers Ma. Franco Carrillo and Amada Agurto Galarza located in the parish of the canton Machala Machala, province of El Oro, during the academic year 2012 - 2013. counted with a population consisting of 123 children aged 4-5 years age and 14 teachers ranging from pre. The research makes an analysis of the incidence of the game in the psychomotor development of children, analyzing the methodological teaching strategies currently used in Early Education Center under investigation. Detected the problem thanks to exploratory research we proceed to the construction of the theoretical framework to properly substantiate the research variables and test the hypotheses. Once the research methodology established appropriate tools for processing the same as that used for quantitative and qualitative analysis of the variables investigated, proceeding then to statistically analyze the data, being able to establish findings and recommendations are made relevant. Depending on the results of the investigation proceeds to raise the proposed solution, the same which provides an educational guide Games that will serve to strengthen the methodology that teachers can use with children to promote the psychomotor development of its students .